Correlation Of Clinical Disease Activity Index And Disease Activity Score-28 in Indonesian Rheumatoid Arthritis Patients - Mochamad Pasha; Harry Isbagio; Zuljasri Albar; Cleopas Martin Rumende (Indonesian Journal of Rheumatology, 2017)
Background:Clinical Disease Activity Index (CDAI) stands out amongst other methods in measuring disease activity of rheumatoid arthritis (RA) patient. CDAI is considered to be more practical and cost-effective in daily practice because it requires no laboratoryexamination. Previous studies conducted overseas revealed that CDAI has good correlation compared to other scoring index in measuring RA disease activity. However, those studies only included pure RA patients without any comorbidity diseases. Indonesian RA patients have distinct clinical profile, in terms of comorbidity conditions, and genetic predisposition which affect the fenotype of the disease.Objectives: Analyze correlation between CDAI compared to Disease Activity Score 28 CRP (DAS28- CRP) in measuring RA disease activity of RA patients in Indonesia.Methods: We conducted a cross sectional study to RA patients who visited rheumatology clinic at Cipto Mangunkusumo general hospital from April to May 2016. Data collected included history of illness, physical examination, and recent laboratory results. All data were documented in reseach’s form. Both CDAI and DAS28- CRP were measured in each patient by two observers. Correlation analysis between two numeric datas fromCDAI and DAS28-CRP were measured with Spearman’s Rho. Overall performance was analyzed as additional results using R2 index.Result: A total of 119 subjects were included in this study. All subjects were RA patients with comorbidities and were representing quite numbers of Indonesian races characteristic profile. Spearman’s Rho = 0,918 and R2 index =0,831 (83,1%).Conclusion: There is positive correlation result between outcome of CDAI and outcome of DAS28-CRP in assesing disease activity of Indonesian RA patients.Key Word: rheumatoid arthritis, Indonesia, correlation,Clinical Disease Activity Index.